Uplink/Downlink Duality in Multi-Cell MU-MIMO Systems with Hardware Impairments - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (WSA 2016; 20th International ITG Workshop on Smart Antennas, 2016)
In this paper, we propose an uplink/downlink duality framework for multi-cell multi-user multiple-input multiple-output (MU-MIMO) systems with residual hardware impairments (HWIs) at the base station and the user terminals. By employing the proposed uplink/downlink duality framework, complex downlink optimization problems can be transformed to equivalent dual uplink problems which are easier to solve. Thereby, for the same total transmit power, the same per-user signal-to-interference-plus-noise ratios (SINRs) are achieved in downlink and uplink. We apply the proposed uplink/downlink duality, and derive a multi-cell HWI aware minimum mean square error (MCHWA-MMSE) precoder. Our simulation results show that the proposed MCHWA-MMSE precoder achieves a substantially higher sum rate than conventional MMSE and conjugate beamforming precoders.<br